Search for mixing-induced CP violation using partial reconstruction of B[bar]0→D(*)+Xl[iota]-νl[nu][bar][iota] and kaon tagging - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review, 2016)
We describe in detail a previously published measurement of CP violation in B0-¯B0 oscillations, based on an integrated luminosity of 425.7 fb−1 collected by the BABAR experiment at the PEPII collider. We apply a novel technique to a sample of about 6 million ¯B0→D*+ℓ−¯νℓ decays selected with partial reconstruction of the D*+ meson. The charged lepton identifies the flavor of one B meson at its decay time, the flavor of the other B is determined by kaon tagging. We determine a CP violating asymmetry ACP=(N(B0B0)−N(¯B0¯B0))/(N(B0B0)+N(¯B0¯B0))=(0.06±0.17+0.38−0.32)% corresponding to ΔCP=1−|q/p|=(0.29±0.84+1.88−1.61)×10−3. This measurement is consistent and competitive with those obtained at the B factories with dilepton events.